Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1021/acs.jafc.0c06730
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarum 69-2 Combined with Galacto-Oligosaccharides Alleviates d-Galactose-Induced Aging by Regulating the AMPK/SIRT1 Signaling Pathway and Gut Microbiota in Mice

Abstract: Probiotics and prebiotics for preventing and alleviating the degenerative changes associated with aging have received extensive attention. In the present work, Lactobacillus plantarum (L. plantarum) 69-2 with the highest antioxidant capacity combined with galacto-oligosaccharide (GOS) was used in aging model mice to evaluate the effect on aging and the regulation of gut microbiota. The combination of L. plantarum 69-2 and GOS supplementation could significantly (P < 0.05) improve liver function, antioxidant ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 50 publications
0
40
0
Order By: Relevance
“…Therefore, it is necessary to clarify the mechanism of SIRTs in HCC. The above research results all demonstrate the mechanism by which SIRT1 participates in the body, and it may be possible to make a breakthrough in the treatment of HCC in the future [116]. Additionally, many studies have provided insight into the effects of the clustered regularly spaced short palindrome repeats/CRISPR-associated protein 9 system (CRISPR/Cas9) on SIRT biology, and SIRT editing has shown its relevance to tumors in the latest research.…”
Section: Conclusion and Prospectivementioning
confidence: 75%
“…Therefore, it is necessary to clarify the mechanism of SIRTs in HCC. The above research results all demonstrate the mechanism by which SIRT1 participates in the body, and it may be possible to make a breakthrough in the treatment of HCC in the future [116]. Additionally, many studies have provided insight into the effects of the clustered regularly spaced short palindrome repeats/CRISPR-associated protein 9 system (CRISPR/Cas9) on SIRT biology, and SIRT editing has shown its relevance to tumors in the latest research.…”
Section: Conclusion and Prospectivementioning
confidence: 75%
“…Studies indicate that probiotics can rebuild the intestinal microbial community, increase the colonization of probiotics such as Lactobacillus in the intestinal tract, and protect and improve the integrity of the intestinal barrier [41,42]. Wan found that L. plantarum 69-2 and GOS could activate the hepatic AMPK/SIRT1 signaling pathway by regulating the gut microbiota and metabolites through the liver-gut axis to restore hepatic antioxidant activity in order to alleviate aging [43]. Probiotics regulate the growth of bacteria in the intestinal tract and combine with intestinal toxic molecules to reduce the level of bacterial urea retention in molecules [44].…”
Section: Discussionmentioning
confidence: 99%
“…GOS regulates the gut microbiota and its metabolites through the liver-gut axis. GOS fermentation significantly increases butyrate acid levels, which can activate the hepatic adenosine 5'-monophosphate (AMP)-activated protein kinase (AMPK)/SIRT1 signaling pathway, increase SIRT1 expression, restore hepatic antioxidant activity, and alleviate aging [ 94 ]. However, there is no direct evidence that acarbose affects the SIRT6 longevity gene.…”
Section: Putative Gut Microbiota-mediated Mechanisms For the Extensio...mentioning
confidence: 99%